Characteristics of Oxidative Storage Stability of Canola Fatty Acid Methyl Ester Stabilised with Antioxidants - Tirto Prakoso; Parncheewa Udomsap; Akiko Tanaka; Toshihiro Hirotsu; Shinichi Goto (Institute for Research and Community Services, Institut Teknologi Bandung, 2012)
The storage effects on the oxidation characteristics of fatty acid methyl ester of canola oil (CME) were investigated in this study.CME stabilised with two antioxidants, i.e.2,6-di-tert-bytyl-p-cresol (BHT) and 6,6-di-tert-butyl-2, 2'-methylendi-p-cresol (BPH), was stored at 20, 40 and 60°C.The oxidation stability data were measured by the Rancimat test method and it was found that both BHT and BPH addition increased the oxidation resistance of the CME. The results showed that when BPH or BHT was added at a concentration of 100 ppm, the oxidation induction period of the neat CME samples increased from 5.53 h to 6.93 hand 6.14 h, respectively. Comparing both antioxidants, BPH proved to be more effective in increasing the oxidation resistance when both antioxidants were added at the same concentration. Furthermore, the oxidation induction timedecreased linearly with the storage time. It was shown that the oxidation occurred rapidly in the first 8 weeks of storage. Later, a kinetic study was undertaken and first-order kinetics were applied to explain the oxidation characteristics of the CME added with antioxidants. This kinetic study focused on exploiting the activation energy values obtained from the Arrheniusequations. Also, the oxidation effects on other quality parameters, including acid value, peroxide value, kinematic viscosity, and water content, were examined.